Pengaruh Kepemimpinan, Communication Skill dan Trust terhadap Kinerja Pegawai pada Sekretariat DPRD di Kabupaten Agam - Dewi Afriani; Yulihasri Yulihasri (Jurnal Mirai Management, 2023)
This study aims to determine and analyze the influence of leadership, communication skills and trust together on the performance of employees at the DPRD Secretariat in Agam Regency. A sample of 56 employees was determined using a saturated sampling technique. This type of research is quantitative research. Data collection techniques using a questionnaire with a Likert scale model with 5 alternative answers. Data analysis was performed by multiple regression analysis. The results of the study show that (1) leadership has a positive and significant effect on employee performance. (2) Communication Skill has a positive and significant effect on employee performance. (3) Trust has a positive and significant effect on employee performance. (4) Leadership, communication skills and trust together have a significant effect on the performance of employees at the Agam Regency DPRD Secretariat. Keywords: Leadership, Communication Skill, Trust